Vaginal histology of buffalo cows during their productive and reproductive activity - Oba, E. [UNESP] (2010)
Knowing the productive and reproductive characteristics of buffalo cows is a basic requirement to implement a selective process and to evaluate the fertility conditions of females. This experiment aimed at characterizing the histological aspects of the vaginal mucosa during their productive and reproductive activity. Twenty four healthy buffalo cows were used. Vaginal samples (biopsies) were collected at different phases of the cycle. In this study, it was observed and evaluated the following histological aspects: description of vaginal epithelium, thickness, amount of epithelium layers, amount of crypts and wedges. The histological findings were as follows: 39.82±11.92, (variation coefficient (VC) = 29.05%); 5.05±1.52 layers, (VC = 30.06%); 0.71±0.56 crypts, (VC = 79.32%); and 0.77±0.76 wedges, (VC = 98.25%), respectively, for the epithelium thickness, amount of layers, crypts and wedges. Average epithelium height was lower during the anestrus and higher during the estrus. Similarly, the number of epithelial cell layers was higher during estrus. The presence of crypts was evident during all phases, but lower during metaestrus. Leukocyte infiltration was constant finding during all studied phases. PAS positive reaction was observed throughout the phase, being more evident during estrus. Chorionic edema was observed from the 5th to the 8th month of pregnancy and during estrus.